Thematic Review of Teaching Phonics and Phonemic Awareness in Early English Literacy - Mahmuda Aktar Hasu (Journal of Applied Linguistics, 2026)
Early literacy is a vital component of children’s academic development, especially in ESL, EFL and multiligual process. Phonics and Phonemic awareness both are key elements that support further decoding, word understanding, and reading comprehension. This study aims to review and interpret what has so far been found regarding phonics and phonemic awareness as early development blocks for English literacy, particularly in EFL, ESL, and multilingual learning environments. Although two key concepts, phonics and phonemic awareness, provide a basis for teaching about how letters represent sounds, research into these interlinked areas of study has emerged across a wide range of languages and teaching settings. In addressing the gap, the paper relies on a thematic literature review approach and reviews 44 articles that have appeared in accredited peer-reviewed research journals from 2020 onwards. The reviewed studies were included in a thematic analysis to synthesize common themes about language-based sources of early literacy: instructional efficacy, and classroom practice. The results suggest that phonemic awareness has a vital cognitive and linguistic function in early reading, including enabling the development of phonological processing skills, word recognition, and decoding. Phonics teaching was also seen to be most effective when it was explicit, systematic, and developmentally appropriate, especially when combined with the spoken language. Moreover, research findings show that combined instructional methods such as phonemic awareness and phonics produce more enduring literacy outcomes than stand-alone methods do, particularly among beginning readers and students who are learning in multi-linguistic contexts. The study raises the significance of including linguistically informed literacy instructions in early childhood curricula and teacher education. The current study also highlights the need for longitudinal investigations that explore how long-term literacy outcomes develop amongst different educational situations. Keywords : Phonemic awareness; phonics instruction; early literacy development; EFL context; ESL classrooms.